Occurence and risk factors of tuberculosis infection in orphanage children in Bali - Clearesta, Kartika Eda; Mayangsari, Ayu Setyorini Mestika; Wati, Dyah Kanya; Purniti, Ni Putu Siadi; Suwarba, I Gusti Ngurah Made; Artana, I Wayan Dharma (Paediatrica Indonesiana, 2024)
Background Tuberculosis (TB) is an infectious disease that is still a common threat worldwide, especially in pediatric populations. TB transmission occurs particularly when the transmitter has no obvious manifestation of the disease. There is a higher incidence of TB infection in children than in the general population, especially in high risk populations such as children in orphanages. However, the incidence of TB infection in orphaned children in Indonesia, including Bali, is unknown. Objective To describe the incidence and risk factors for TB infection in children in orphanages in Bali. Methods This case-control study was conducted in 12 orphanages in Bali. Subjects were divided into a case group comprised of children with TB infection, and a control group comprised of those without TB infection. TB infection was diagnosed by positive tuberculin test without clinically confirmed TB. Results A total of 175 children were recruited as subjects. There were 49 (28.0%) children with TB infection. Bivariate analysis revealed significant associations between density, humidity, ventilation/room area ratio, and area of ??origin with TB infection. Multivariate analysis showed that ventilation/room area ratio and room humidity of ?73% were independently positive correlated with TB infection. Natural lighting and BCG scar were not significantly different between groups. Conclusion The occurence of TB infection in children residing in orphanages in Bali is high (28%). The risk factors identified independently are lower ventilation and higher room humidity.